2015
DOI: 10.1111/andr.12123
|View full text |Cite
|
Sign up to set email alerts
|

The immobilization of human spermatozoa bySTAT3 inhibitory compound V results from an excessive intracellular amount of reactive oxygen species

Abstract: We previously showed that Stattic V (Stat3 inhibitory compound V) reduces human sperm motility and cellular ATP levels, increases intracellular Ca 2+ concentration, and promotes mitochondrial membrane depolarization resulting in increased levels of extracellular reactive oxygen species (ROS). As these alterations in cellular function are highly similar to what is observed in a cell undergoing apoptosis, our goal was to determine if the immobilizing effect of Stattic V on spermatozoa results from apoptosis or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Actually, the fact that the NAC exhibits an isoelectric point equal to 5, makes the treatment more effective in acidic environments, canceling its effects under the typical alkaline conditions of ascidian sperm. In the human, previous studies 57 found that 0.5 mM NAC prevented sperm immobilization induced by Stat3 inhibitory compound V (Stattic V) as well as the production of superoxide anion, mitochondrial membrane depolarization and the oxidation of protein free thiols caused by Stattic V; however, with regards to pH i , 0.5 mM NAC did not significantly affect pH i but efficiently counteracted Stattic V-induced acidification.…”
Section: Discussionmentioning
confidence: 87%
“…Actually, the fact that the NAC exhibits an isoelectric point equal to 5, makes the treatment more effective in acidic environments, canceling its effects under the typical alkaline conditions of ascidian sperm. In the human, previous studies 57 found that 0.5 mM NAC prevented sperm immobilization induced by Stat3 inhibitory compound V (Stattic V) as well as the production of superoxide anion, mitochondrial membrane depolarization and the oxidation of protein free thiols caused by Stattic V; however, with regards to pH i , 0.5 mM NAC did not significantly affect pH i but efficiently counteracted Stattic V-induced acidification.…”
Section: Discussionmentioning
confidence: 87%
“…In vitro studies evaluated the effect of NAC on human spermatozoa using Stattic V, a non-peptidic inhibitor of STAT3 involved into sperm function [84,85]. Stattic V is associated to sperm apoptosis and sperm immobilization due to increase of different pathological outcomes such as acrosome reaction, intracellular Ca 2+ concentration, extracellular levels of reactive oxygen species (ROS), mitochondrial membrane depolarization and decrease in sperm ATP content [86]. Other in vivo study assessed the effect of 600 mg/day of NAC for three months to evaluate different parameters as chromatin negative alteration induced by high oxidative stress and its consequences on sperm quality (motility, count and morphology).…”
Section: N-acetylcysteninementioning
confidence: 99%
“…The significantly elevated levels of homocysteine observed in the spermatozoa of patients who exhibit severe disruptions to their semen protein-including asthenozoospermia, asthenoteratozoospermia, and oligoastheno teratozoospermia (Kralikova et al, 2017)-could reflect the ability of homocysteine to create a state of oxidative stress following conversion to thiolactone and subsequent activation of mitochondrial ROS generation. Similarly, the recent observation that Stattic V, an inhibitor of Signal transducer and activator of transcription 3, will trigger mitochondrial ROS in mammalian spermatozoa(Lachance, Goupil, Tremblay, & Leclerc, 2016) is probably a reflection of this compound's ability to form adducts with proteins (potentially in the electron transport chain) via thiol-mediated Michael addition reactions. The fact that N-acetyl-L-cysteine inhibited the ROSinducing properties of Stattic V would be in keeping with such a thiol-adduct formation mechanism(Lachance et al, 2016).…”
mentioning
confidence: 99%
“…Similarly, the recent observation that Stattic V, an inhibitor of Signal transducer and activator of transcription 3, will trigger mitochondrial ROS in mammalian spermatozoa(Lachance, Goupil, Tremblay, & Leclerc, 2016) is probably a reflection of this compound's ability to form adducts with proteins (potentially in the electron transport chain) via thiol-mediated Michael addition reactions. The fact that N-acetyl-L-cysteine inhibited the ROSinducing properties of Stattic V would be in keeping with such a thiol-adduct formation mechanism(Lachance et al, 2016).…”
mentioning
confidence: 99%